Educational Media Communication Post Covid-19 Pandemic: Study of Media Convergence in Multicultural - Suko Widodo; Kristama, Baswara Yua (Jurnal Spektrum Komunikasi, 2024)
The goal of this research-based, scientific study is to shed light on how Surabaya's campuses and schools are prepared to handle the demands of modern, convergent digital media and learning methodologies. This study focuses on the in-person teaching and learning process that is scheduled to resume in July 2021 and reshaping society three years after the pandemic. Even while face-to-face instruction will introduce new habits for the new era—the new norm era—schools and campuses must nonetheless adhere to government-established health procedures. The education industry has updated its teaching strategies for this new normal period.  Schools and colleges use information and communication technology-based teaching and learning strategies both online and offline to keep up the teaching and learning process. The issue is that, from facilities to human resources (HR), Indonesian campuses and schools are currently not dispersed equally, especially in major cities like Surabaya. This presents a significant obstacle to Indonesia's educational system. In order to characterize the discourse and social changes that take place during the preparation process of learning techniques employing convergent digital media in the city of Surabaya, this study employs a discourse analysis method with a descriptive qualitative approach. The study's findings and recommendations indicate that, in the new normal period, digital communication media is presently a useful and efficient tool for learning. The new normal era's social shifts in the education sector today base its teaching strategies on the convergence of media and digital technologies.